2018
DOI: 10.5547/01956574.39.6.pbou
|View full text |Cite
|
Sign up to set email alerts
|

Antidumping and Feed-In Tariffs as Good Buddies? Modeling the EU-China Solar Panel Dispute

Abstract: The paper analyzes the interactions between trade and renewable energy policies based on the EU-China solar panel dispute which is the most significant antidumping (AD) complaint in Europe. We build a price competition duopoly model with differentiated products and intra-industry trade in photovoltaic (PV) equipment. We show that an optimal antidumping duty always increases with the feed-in tariff (FIT) program set in the home country. An appropriate antidumping duty-nullifying the dumping margin-decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The emergence of TTBs as the new form of protectionism is one of the most remarkable changes in the international trade system during the past decades [5][6][7][8][9]42]. The trend of employing TTBs as effective remedy actions against imports has become exceedingly popular [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of TTBs as the new form of protectionism is one of the most remarkable changes in the international trade system during the past decades [5][6][7][8][9]42]. The trend of employing TTBs as effective remedy actions against imports has become exceedingly popular [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…During the process, promoting policies, for example, FiT and RPS, have been key to the vast diffusion, as they are in force in an increasing number of countries and regions (Olmos et al, 2012;Smith and Urpelainen, 2013;Shrimali et al, 2015). The trade dispute on RE products between the EU and China shows the significant effect of the policy on demand for the components (Bougette and Charlier, 2018).…”
Section: Yasuhiro Oguramentioning
confidence: 99%
“… Mouzam et al (2016) empirically studied the anti‐dumping duties imposed by India on Chinese raw silk and the impact of this measure. Bougette and Charlier (2018) focused on the EU–China solar panel trade frictions and studied the price competition in duopoly markets with differentiated products. Hübler and Herdecke (2020) showed that US car tariffs are a credible threat to the EU, and China suffers from the US latest extended, tightened tariffs.…”
mentioning
confidence: 99%